Some indicators in rat blood samples taken from the portal vein and the inferior vena cava after consumption of different edible fats - Levitsky, Anatoly; Maykova, Anna; Makarenko, Olga (Journal of Education, Health and Sport, 2018)
Purpose: To determine the number of biochemical parameters in rats’ serum derived from the portal vein and the inferior vena cava after consuming edible fats with different fatty acid composition. Methods: White laboratory rats have been receiving in addition to standard vivarium diet 15% of the following edible fats for the 64 days: ordinary sunflower (high- linolenic), high oleic sunflower oil, butter, palm oil and coconut oil. At the end of this period, the rats’ blood was taken under thiopental anesthesia from the portal vein and the inferior vena cava. Determination of elastase activity, alanine aminotransferase, urease, lysozyme, catalase, MDA content were conducted in the obtained serum and the degree of dysbiosis was calculated. Results. The study showed that the activity of urease in serum of blood from the portal vein and the inferior vena cava was increased after consumption of all fats, except high-oleic sunflower oil. The activity of lysozyme, on the contrast, was decreased after feeding rats with butter, palm oil and coconut oil. The decrease of the activity of urease and elastase and an increase in the level of MDA and activity of alanine aminotransferase found in the serum of blood sample from the inferior vena cava, which indicated the involvement of the liver in that processes. The conclusion. High-fat diets, except diet reach in high oleic sunflower oil, increased the degree of dysbiosis in rat’s blood. The greatest increase was observed after the consumption of palm oil. The performed work allowed us to recommend the introduction of high oleic sunflower oil into a diet and reduction of a consumption of products containing palm oil to a minimum amount in order to prevent dysbiosis.